Performance evaluation of texture measures with classification based on Kullback discrimination of distributions - Ojala, T.; Pietikainen, M.; Harwood, D. (Pattern Recognition, 1994 12th International Conference On. Vol. 1, 1994)
This paper evaluates the performance both of some texture measures which have been successfully used in various applications and of some new promising approaches. For classification a method based on Kullback discrimination of sample and prototype distributions is used. The classification results for single features with one-dimensional feature value distributions and for pairs of complementary features with two-dimensional distributions are presented.